Work Hardcore: Reddit's r/elonmusk as Ideological Apparatus of the Silicon Valley Ethic - Leinonen, Valtteri (My University, 2023)
This thesis looks at how the Reddit subforum of r/elonmusk relates to and potentially participates in the ideological promotion of work values associated with what is known as the Silicon Valley work ethic. The Silicon Valley work ethic is a set of dominating work practices originating from California’s hub of technology startup companies and applied by billionaire-entrepreneur Elon Musk at his respective companies. Musk himself claims to work over 100 hours a week and to regularly sleep at his offices, while using this complete dedication to work to realize grand humanity-saving missions. Such practices are also expected of the employees at Musk’s companies which include Tesla, SpaceX, and most recently the social media company Twitter. At focus in the thesis is to see how Reddit users on r/elonmusk – an online social media forum dedicated to Musk and his companies – discuss these intense and subjugating work practices and whether they come to support them in their overall argumentation on the issue. The question is of ideological influence that Musk wields over his considerable following of geek-y online admirers who populate the forum. The work practices of the Silicon Valley ethic enforce structural hierarchies of domination by making workers accept unpaid overtime, long hours, and a lack of a clear work-life balance. Musk’s promotion of these values in the media makes them more accepted and embraced as real-life practices in tech startups and companies. The primary research question of the study is whether r/elonmusk in its debate on the work practices at Musk’s companies ends up operating as a further ideological apparatus in service of the ethic and thus socializing its visitors into embracing the ethic’s values. The thesis also explores as a secondary issue as to whether the r/elonmusk forum acts as an online echo chamber for admirers of Musk that insulates itself away from any critique or negative sentiment posted on the forum about Musk. In the study, I focus on three r/elonmusk posts made about an internal memo sent by Musk to employees of Twitter where Musk demands his new employees to work “extremely hardcore” as well as “long hours at high intensity” in a summation of Silicon Valley work principles. These posts and their most prominent arguments are approached with a framework of materialist ideology-theory which spans scholars from Karl Marx, Antonio Gramsci, Louis Althusser, Projekt Ideologie-Theorie and its acolytes to Stuart Hall. Critical tools of this materialist tradition will allow us to see how both Musk and Reddit as material ideological actors with capitalist profit-motives are able to shape the discussions had on r/elonmusk. I argue that social media and ideology should be approached in media studies in general through this materialist framework and its method of critical intervention into ideological phenomena. This argument is in opposition to debate had recently on ideology as a critical tool in the journal Media, Culture & Society as well as the idealist formulations of Christian Fuchs. Through the analysis of the argumentation and discussion practices present on r/elonmusk, I argue that the forum does act as an ideological apparatus for the Silicon Valley work ethic. I argue that the forum acts as a site of common sense processing for Musk’s geek-y followers, who are also ideologically interpellated by Reddit’s dominant culture of white masculinity and geek-y interests. There is also criticism of the Silicon Valley ethic on the forum and in this openness to critique the forum can not be argued to have an encoded ideological message about the ethic. In its admiration of Musk, however, the forum shows signs of echo chamberization in moderating away personal criticism of Musk and by being influenced in its overall discussion culture by Musk’s joke-y online persona.
Keywords: Reddit, Elon Musk, r/elonmusk, Silicon Valley work ethic, materialist ideology-theory, online echo chamber, Stuart Hall, Projekt Ideologie-Theorie, social media, ideology